Thermal Performance of a Helical Coil Heat Exchanger Utilizing Nanofluids: A Review - Mustafa Abdullah; Adnan Hussein (Journal of Heat and Mass Transfer Research, 2023)
The manufacturing process of heating systems involves incorporating various heat exchangers, each with distinct characteristics. Among these, the helical heat exchanger stands out due to its space-efficient design and enhanced heat transfer rate compared to other variants. Recently, heat exchangers have witnessed novel nanofluid explorations aiming to replace conventional working fluids. Nanofluids possess unique properties that hold the potential for substantial improvements, consequently influencing the efficiency of heat exchangers employing them. The effectiveness of these heat exchangers is intrinsically tied to the properties of the employed nanofluids. Recent years have witnessed remarkable strides in comprehending the distinct traits exhibited by diverse nanofluids. This comprehensive study amalgamates findings from multiple investigations focused on helical-tube heat exchangers utilizing nanofluids as the primary medium. Notably, it underscores the existence of varying conclusions and perspectives among different researchers. This variance arises from the complexity of nanofluid behavior and its interactions within heat exchangers. Consequently, the efficacy of helical heat exchangers leveraging nanofluids hinges on the specifics of the chosen nanofluid and its characteristics. This subject continues to stimulate vigorous research and discussions among scholars. In summation, the dynamic landscape of heat exchanger innovation has brought the spotlight onto helical heat exchangers and their integration with nanofluids, showcasing the intricate interplay between fluid properties and efficient heat exchange.